Analisis Manufacturing Cycle Affectiveness Pada Produksi Kusen Jendela Untuk Meminimalisir Non Value Added Activity - Mashabai, Ismi; Oktariani , Dila; Adiasa, Iksan (Universitas Muhammadiyah Sorong, 2026)
CV. Tunggal Putri, a window frame manufacturer in Sumbawa, faces challenges with production delays that affect customer satisfaction. This study analyzes the effectiveness of its production cycle using the Manufacturing Cycle Effectiveness (MCE) method to reduce non-value-added activities. The research methods include field observation, work time measurement, data adequacy and uniformity tests, and analysis with fishbone diagrams and the 5W+1H approach. The findings show that value-added activities account for 14.98% (19.7 minutes), while non-value-added activities dominate at 80.92% (106.42 minutes), mainly due to waiting for delayed processes. Necessary but non-value-added activities, such as machine setup and material transport, represent 4.09% (5.39 minutes). Interviews with the production head identified three root causes from the fishbone diagram—machine, method, and human factors. The circular saw machine often breaks down due to overheating and wood dust accumulation, while ineffective methods and human errors further contribute to inefficiencies. The study highlights that non-value-added activities significantly reduce production efficiency. After analysis and proposed improvements, production effectiveness increased, demonstrating that the MCE method is effective in identifying and minimizing wasteful activities. In conclusion, applying MCE helps improve efficiency and reduce production time, thereby enhancing customer satisfaction and competitiveness in window frame manufacturing at CV. Tunggal Putri.